Islands of Inquiry: Colonisation, seafaring and the archaeology of maritime landscapes (TA29) Colonisation, seafaring and the archaeology of maritime landscapes - Clark, Geoffrey; Leach, Foss; O'Connor, Sue (Terra Australis, 2008)
This collection makes a substantial contribution to several highly topical areas of archaeological inquiry. Many of the papers present new and innovative research into the processes of maritime colonisation, processes that affect archaeological contexts from islands to continents. Others shift focus from process to the archaeology of maritime places from the Bering to the Torres Straits, providing highly detailed discussions of how living by and with the sea is woven into all elements of human life from subsistence to trade and to ritual. Of equal importance are more abstract discussions of islands as natural places refashioned by human occupation, either through the introduction of new organisms or new systems of production and consumption. These transformation stories gain further texture (and variety) through close examinations of some of the more significant consequences of colonisation and migration, particularly the creation of new cultural identities. Afinal set of papers explores the ways in which the techniques of archaeological science have provided insights into the fauna of islands and the human history of such places. Islands of Inquiry highlights the importance of an archaeologically informed history of landmasses in the oceans and seas of the world.